Do diligent independent directors restrain earnings management practices? Indian lessons for the global world - Nimisha Kapoor; Sandeep Goel (Asian Journal of Accounting Research, 2019)
The purpose of this paper is to explore the role of independent directors’ diligence in restraining earnings management practices in the Indian context.It employs a panel data analysis to test the association of earnings management with the diligence of independent directors.The results suggest that the diligence of independent directors has a significant impact on earnings management. The findings support the agency theory and provide evidence of the role played by the board processes in restricting earnings management.This study is important for the regulators as it highlights the significance of independent directors’ diligence in producing higher quality financial statements, thereby creating the real economic value of companies. This is the first article that explores the impact of independent directors’ diligence on earnings management practices particularly in the context of an emerging economy, like India in the light of new Companies Act 2013 and revised Clause 49 of the Listing Agreement, 2014 by Securities and Exchange Board of India.